Measuring the Efficiency of Health Services in Lower‐income Countries: The Case of Papua New Guinea. (March 2014) - Au, Nicole; Hollingsworth, Bruce; Spinks, Jean
<x xml:space="preserve">Abstract</x> Papua New Guinea (PNG) faces enormous health challenges and information concerning how to allocate limited health resources efficiently is lacking. This article finds that geographical location is important in achieving higher efficiency scores. In addition, it compares efficiency scores against a range of quality indicators. The results demonstrate that different conclusions are reached when efficiency scores are assessed in the context of broader health system objectives. Analyses of this kind can provide valuable information to policy‐makers in lower‐income countries.